Human-Robot Interaction Using ROS Framework for Indoor Mapping Missions - M.S., Hendriyawan Achmad; Mohd Razali, Daud; Saifudin, Razali; Pebrianti, Dwi (Universiti Malaysia Pahang, 2016)
The necessity of effective integration tools in robotics research play an important scientific contribution and highly recommended. However, robotics researchers have limited time during the experiments with definite targets and ultimately there is no choice but to use integration tools as software framework to avoid re-inventing the wheels. This research examines how humans work with teleoperated unmanned mobile robots to perform interaction in order to explore and build an indoor map by utilizing robotic software framework known as Robot Operating System (ROS). ROS infrastructure tools are involving together from the file system level to the community level,enables independent decisions about development and implementation. These experiments focus on two major area; the way human delivers the targets coordinate to the robot using ROS framework, and the way robot conducts SLAM as a feedback to the human related to current location and occupied map within ROS platform. Hector SLAM plays an important role in 2D localization using 2D LIDAR sensor which is needed by Octomap in order to construct 3D mapping simultaneously using Kinect sensor. The results showed that human-robot interaction using the ROS-based teleoperated system for mapping task is easy to configure and propose an effective tool in term of large-scale service robot development.